"A Girl Worth Fighting For" : Transculturation, Remediation, and Cultural Authenticity in Adaptations of the "Ballad of Mulan" - Giunta, Joseph V. (SARE: Southeast Asian Review of English, 2018)
Since its first feature-length film, Disney has been (ab)using beloved folktales and legends by revising them to its corporate predilections. Amassing billions of dollars in the process, it has not taken into account the alternate pedagogies and surrogate histories created as a result. Under the guise of “experts” and creators of “timeless classics,” Disney has been able to prosper by drastically altering texts that are culturally significant and prevalent. Focusing on one particular film, Disney’s 1998 feature, Mulan, I will demonstrate how Disney, through its creation of what it would defend as a satiation of global tastes, is instead crafting alternate narratives that no longer convey the original text’s message or meaning. Though the main source text of Disney’s animated feature is Robert San Souci’s Fa Mulan: The Story of a Woman Warrior, both of these texts (film and children’s book) are adaptations of the “Ballad of Mulan”, an ancient poem that traces back to the Chinese Southern and Northern Dynasties. The range of positions adopted by the composers of these two texts (with the Ballad as the original) not only demarcates retelling, adaptation, and remediation, but also bears consideration of outsider authorship and seems to indicate divergent sensibilities and authoritative relationships. The transformations engendered by these contrasting iterations of Mulan (self-interested fairytale princess, warrior woman, filial daughter) compel an investigation into the sociocultural and pedagogical influence of each of these respective mediums (animated film, children’s literature, poetry), while also unmistakably sullying Disney as the iniquitous adapter.